Identifying key factors affecting novice players learning of soccer skills - Al-Asadi, M. (International Journal of Sports Science, 2016)
Acquiring a skill has always been linked to various factors in sport field. The literature showed that there is a lack of studies to address the factors that would drive novice players to learn soccer skills. Performing complex skills is typically the main concern of most novice players because of its role in a game play. Therefore, this paper reviewed some previous studies in the field of sport education to gain the sufficient insights about these factors in learning situation. A holistic view of these factors and the relation between them are presented in this paper. Such view can help enrich the current body of knowledge about how to formulate a sufficient environmental conditions for learning soccer skills among novice players.